Persistent Left Superior Vena Cava in a Hemodialysis Patient - Dalirani, Reza; Mirzaee, Mahbubeh; Porpashang, Paniz; Seifi, Atena (Journal of Pediatric Nephrology, 2022)
We report a case of end-stage renal disease with a persistent left superior vena cava (PLSVC) after placement of hemodialysis (HD) catheter through the left internal jugular vein as revealed on routine post-procedure chest X-ray. The diagnosis of PLSVC was confirmed by echocardiography and thorax computed tomography. This anomaly is rather rare, and few studies have evaluated the safety of PLSVC for HD. The catheter was used for 2 months under careful continuous monitoring with no complications. Physicians who place HD catheters in the left jugular/subclavian vein should be aware of the possibility of PLSVC.